Exploring the Relationship between Entrepreneurial Orientation and Performance of Agribusiness SMEs in Balikpapan - Nainggolan, Ananda Fitriana; Patiung, Markus; Susilo, Achmadi (PT. Sangadji Media Publishing, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are integral to Indonesia's economic development, comprising a vast majority of national business entities and significantly contributing to the GDP. Despite their importance, MSMEs face challenges in a highly competitive landscape, exacerbated by foreign competition. This study focuses on Agribusiness MSMEs in Balikpapan City, aiming to analyze their entrepreneurial orientation and business performance while identifying factors influencing this relationship. Employing a quantitative approach, data was collected through structured questionnaires from registered MSMEs. The analysis, conducted using Partial Least Square Structural Equation Modeling (PLS-SEM), reveals that innovation, proactiveness, and autonomy significantly influence business performance, while competitiveness and risk-taking do not. The findings underscore the pivotal role of innovation in enhancing SME performance, providing insights for policymakers and managers to support SME growth and sustainability. Despite its contributions, the study has limitations, including its focus on a specific sector and reliance on qualitative data. Future research could explore comparative studies across industries, integrate quantitative methods, and investigate the role of government policies in fostering SME innovation. Overall, this research contributes to understanding the relationship between innovation and SME performance, guiding strategies to support SMEs in Balikpapan and beyond.